ANALYSIS OF THE IMMEDIATE RESULTS OF THE MULTIMODAL METHOD OF BREAST CANCER THERAPY IN COMPARISON WITH THE RESULTS OF CONVENTIONAL THERAPY - Djakhongir R. Sabirov; Mirza A. Gafur-Akhunov; Oybarchin J. Yusupova (Central Asian Journal of Medicine, 2023)
An analysis of the immediate results of the multimodal method of breast cancer therapy in comparison with the results of traditional therapy showed that at the initial stages of breast cancer (BC), the applied non-traditional therapy, accompanied by immunocorrective drug therapy with preliminary exposure to medium frequency radio waves (350 + 15 kHz) is observed lysis of the tumor formation, reduction of the volume of the tumor and affected regional lymph nodes, as well as immunological parameters and improvement of the quality of life of patients. So, in the group on the background of traditional therapy, partial lysis of the tumor was observed on the 21st day, and in the main study group with non-traditional therapy on the 7th day. Clinical efficacy was monitored using clinical, laboratory and instrumental research methods. According to the ECOG and Karnofsky scales, there is a significant improvement in the quality of life in the main group of patients. Therefore, the advantage of the multimodal method of therapy was the easy tolerability of treatment procedures, the mild post-drug course of antitumor therapy, the early restoration of functional abilities, and the reduction in the incidence of complications, which ultimately affected the improvement in the quality of life of patients.